Synthesis, Characterization and Anti-Cancer Screening of Some New Coumarin Derivatives and Their Complexes - Dalal. M. Ibrahim (Universiti Sains Islam Malaysia, 2024)
A new series of 6-hydroxy-4-methylcoumarin derivatives ligands namely 6-hydroxy-4-methyl-5-(phenylazo) coumarin (L1), 6-hydroxy-4-methyl- 5- (p-chlorophenylazo) coumarin (L2), 6-hydroxy-4-methyl -5,7- (bis-phenylazo) coumarin (L3) and 6- hydroxy-4-methyl-5,7-(bis-p-chlorophenylazo) coumarin (L4) were successfully synthesized and characterized. The complexation of zinc (II), nickel (II), copper(II), cobalt (II) and manganese (II) with ligands L1, L3 and L4 gave salt type complexes with the formula of M(C16H15O3N4) and M(C22H13O3N4CI2 (where M= Zn, Ni, Cu, Co, Mn) respectively. The compounds were characterized by microelemental analysis, infra-red and nuclear magnetic resonance spectroscopic techniques. The CHN analysis of the ligands are in good agreement with the calculated values. The spectroscopic analysis of the complexes indicated that the ligand coordinated to the metal centres as a bidentate ligand in azocoumarin through the OH group in the aromatic ring. Coordination of the nitrogen atom of the azo group and as polydentate ligand in bis-azocoumarin form a distorted octahedral arrangement around zinc(II), nickel(II), copper(II), manganese(II) centre.The molar conductivity of the divalent metal ions complexes was small which directly supports the fact that all of the investigated complexes are non ionic. These low conductivity values may be attributed to the presence of chloride ions in the coordination sphere rather than ionic association to the metal ions during complex formation. Cytotoxic activity for the ligands and the complexes were evaluated against breast and lung cancer cells, indicate that the compounds possess remarkable cytotoxic effect at low concentration. Cu(II) complexes of L1,L3 and L4 ligands may be one of the new lead compounds for the development of anticancer agents as they show high cytotoxicity with all cell lines at concentration 30µg/ml.